Violence, the sacred, and things hidden : discussion with René Girard at Esprit (1973) - Girard, René, 1923-2015 (Breakthroughs in mimetic theory., 2021)
"In 1973 Girard was invited by the editors of Esprit in Paris to discuss his work with several interlocutors from the fields of philosophy, psychoanalysis, literature, and theology. In this exchange Girard addresses challenges to his thinking, and is further prompted to consider the relation between his critique of primitive or archaic religion and the role of Judeo-Christianity, which Western culture has adopted as its own, and to which his book pays scant attention"--